Development of the sociology of sport in the aspect of theoretical analysis - Lubysheva L.I.; Rosenko S.I. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to pinpoint the trajectory of sociological inquiry in the realm of physical culture and sports, we will examine the content of the journal «Theory and Practice of Physical Culture». Methods and structure of the study. A review of articles on the sociology of physical culture and sports published in the journal Theory and Practice of Physical Culture from 2000 to 2024 was conducted. Results and conclusions. In the present day, the sociology of physical culture and sports has emerged as a distinct discipline, grounded in empirical research and theoretical insights from the field. Sociologists are dedicated to exploring the intricate web of social relationships and interactions within the realm of sports. The evolution of physical culture and sports into a prominent social phenomenon underscores the necessity for ongoing investigation into its current state and future trajectory. Consequently, a comprehensive examination of sociological publications in this domain is crucial for identifying the key areas of contemporary sociological inquiry and their potential future trajectory.